(untitled) (Research, Society and Development, 2023)
The text addresses the importance of cardiac markers, focusing on troponin, in the diagnosis of acute myocardial infarction (AMI). With the aging population and the increase in chronic-degenerative diseases, such as cardiovascular diseases, it is crucial to analyze and study these markers to confirm if the patient is experiencing a heart attack, contribute to treatment, and assist in the prevention of cardiovascular disorders. Troponin is an essential protein in the process of muscle contraction, both in skeletal and cardiac muscle. It consists of three subunits: troponin C, troponin I, and troponin T. Troponins I and T are considered the most relevant markers for the diagnosis of AMI. These proteins are released into the bloodstream after a heart attack and remain elevated for an extended period, detectable through specific tests. Elevated levels of troponin indicate the presence of a heart attack, and its release begins a few hours after the initial symptoms. Detection and interpretation of troponin levels are performed through blood tests. The diagnosis of AMI is established when the troponin concentration exceeds a certain threshold. Besides AMI, troponin can also be detected in other non-cardiac pathological conditions, which should be considered in result interpretation. In summary, the analysis of cardiac markers, especially troponin, plays a fundamental role in the early and accurate diagnosis of acute myocardial infarction. These markers are important for the treatment and prevention of cardiovascular disorders, aiming to increase the population’s survival rate.